Nutritional Composition and Metabolic Effects of Oat Dietary Fiber Extracts on Diabetic and Hypercholesterolemic Male Rats - Bilal, Asmaa; Parveen, Riffat; Kalsoom, Samia (Pakistan Journal of Nutrition, 2014)
The nutritional analysis of raw, ground Oat grain was conducted according to AOAC, 2005. The mean percentage value of various nutrients in Oat was following, protein (12.32%), fat (4.49%), crude fiber (6.06%), ash (3.04%) and moisture 10.01%. The lignin and cellulose content were also assessed; cellulose content being estimated as (4.11%) and lignin as (2.69%). High fiber diet (HFD) for rats was prepared using dietary fiber isolated from raw ground seeds, with some necessary alteration of the basic purified diet AIN-76 (BPD AIN-76) for rats. The rats (n = 36) were equally divided into six groups to study the effect of Oat HFD on serum glucose and serum total cholesterol (TC). Group I comprised on rats with normal blood glucose level fed on basal diet (AIN-76), Group II was Alloxan (ALX monohydrate) induced diabetic rats fed on basic purified diet AIN-76. Group III comprised of diabetic rats fed on Oat HFD. The same research design was replicated to study the cholesterol level, hence Group IV comprised normal rats on BPD AIN-76, Group V was of induced Hypercholesterolemic rats on BPD AIN-76 and Group VI consisted of induced hypercholesterolemic rats on Oat HFD. The random blood glucose level (RBGL) (mg/dL) and TC (total cholesterol) level (mg/dL) were monitored for a period of six weeks. It was observed that Oat had a significant effect on the lowering of RBS level and total cholesterol in the experimental animals.